Improving Discrete Documentation of Cancer Staging—An Alert-Free Approach - Potashner, Renee; Yan, Adam P. (Applied Clinical Informatics, 2025)
Cancer staging is integral to ensuring cancer patients receive appropriate risk-adapted therapy. Discrete cancer staging using a structured staging form helps ensure accurate staging, provides a single source of truth for staging information, and allows for reporting to regulatory authorities. Our institution created pediatric oncology specific discrete staging forms that have been shared with the broader Epic community. By November 2023, baseline utilization of the staging form for patients with leukemia or lymphoma was 43%, and the override rate for our existing alert was 99.9%.Improve discrete documentation of cancer stage for patients with leukemia or lymphoma within 60 days following initiation of chemotherapy to >80% by July 2024 as measured by signed staging form.Model for improving plan-do-study-act (PDSA) cycles was implemented, and statistical process control charts were used to evaluate impact. The first intervention was educational training to oncology providers. The second PDSA cycle involved sharing monthly individual completion data with the primary oncologist regarding their personal patient metrics. The third PDSA cycle involved removing the interruptive alert.Within 6 months, documentation of primary oncologist improved from 86 to 100%, and initiation of staging form improved from 57 to 90%. Completion of signed cancer staging form reached 80%. Patients marked as not needing staging increased from 5 to 17%.Completion of a digital cancer staging form is important for continuity of care, and to facilitate reporting to regulatory authorities, though frequent interruptive alerts were an ineffective method for improving documentation. Education and data sharing increased staging completion to near target, with ongoing efforts to reach the goal of 80%.
Keywords: electronic health records and systems; clinical information system, clinical decision support; clinical information systems, oncology domain; clinical care, pediatrics domain; socio-technical aspects of